Antimicrobial and antioxidant study of combined essential oils of Anethum Sowa Kurz. and Trachyspermum ammi (L.) along with quality determination, comparative histo-anatomical features, GC‒MS and HPTLC chemometrics - S.A. Wasim Akram; Mary Shamya Arokiarajan; J. John Christopher; Mohammad Jameel; Mohd Saquib; Tirumala Santosh Kumar Saripally; Noman Anwar; Mohd Asif; Kabiruddin Ahmed K (Scientific Reports)
Abstract Spices played crucial and variable roles in traditions, culture, history, religious ceremonials and festivals along with fetching food flavor and microbial protection globally due to presence of structurally unique and multi-natured chemotypes. Their existence in dishes portrayed key roles in improving shelf life by regulating spoilage of cuisine with different synergistic mechanism. Histo-anatomically (A) sowa exhibited distinguished cellular attributes which created remarkable differences with T. ammi. HPTLC chemometrics of both fruits revealed several peaks for active metabolomics with unique isocratic combination of menstruum. GC-MS study of hydro-distillate exhibited presence of monoterpenic cyclic and aromatic hydrocarbons, alcoholic and ketonic groups along with phenolic derivative that covers majorly 90% of total metabolites. Combined essential oils (EOs 1 + 2) of both fruits showed excellent antimicrobial activity against various clinical pathogenic strains such as K. pneumoniae at 10 µL/mL, S. aureus at 2.5 µL/mL, E. coli and E. faecalis at 1.25 µL/mL, and MRSA and Bcereus at 0.625 µL/mL and (C) albicans at 0.312 µL/mL as the MIC. The antioxidant study of (EOs 1 + 2) with maximum inhibition percentage to DPPH assay was 84.02 ± 1.05 at 100 µg/mL, and minimal inhibition was 72.31 ± 0.63 at 5 µg/mL with IC50 value 4.69 ± 0.22 µg/mL, while ABTS assay extreme was 79.15 ± 2.14 µg/mL and minimal was 67 ± 1.34 with the IC50 value of 18.37 ± 0.15 µg/mL, in superoxide assay uppermost inhibition was 81.03 ± 0.27 µg/mL and lowest was at 65.16 ± 3.15 with the IC50 value 16.46 ± 0.54, and H2O2 radical scavenging activity, predominant value was 78.01 ± 0.47 and least was 64.1 ± 2.01 with IC50 15.58 ± 0.34. These comparative key diagnostic features and synergistic effect of multicomponent natural antimicrobials will provide profound intellect of ancient utility and further scientists to explore their multiple mechanistic modality and application in food and beverages industry.